A PERAN TQM, BUDAYA ORGANISASI, DAN KEPUASAN KARYAWAN DALAM MENINGKATKAN KINERJA PERUSAHAAN: STUDI PADA HOTEL CLARO MAKASSAR : PERAN TQM, BUDAYA ORGANISASI, DAN KEPUASAN KARYAWAN DALAM MENINGKATKAN KINERJA PERUSAHAAN: STUDI PADA HOTEL CLARO MAKASSAR - Wahyudi Wahyudi (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to determine the effect of total quality management, organizational culture on improving company performance, and the role of employee satisfaction as a mediator between total quality management and company performance. This type of research is explanatory research. The data used in this study is primary data. The results showed that there was a positive and significant relationship between organizational culture on total quality management, and company performance. Likewise, the total quality management variable has a positive and significant effect on company performance. Furthermore, employee satisfaction has a very strong mediating role between total quality management and company performance.Keywords : Total quality management, organizational culture, employee satisfaction, company performanc